(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2016)
This research had the objective of analyzing multidimensional poverty as a deprivation of basic capacities in the homes of San Jacinto community, Barquisimeto, Lara state, during 201 6. The study was based on the Adjusted Counting Mo Index developed by Sabina Alkire and James Foster, and based on Amartya Sen’s capacities theory as a descriptive element of welfare deprivation. The population was composed by 376 houses located within the Marcos Duran communal council scope, and a sample of 71 houses was selected, where aquestionnaire was applied consisting of twenty-eight items, obtaining information from 94 households to measure the dimensions of: Housing, Education, Health, Revenue and Security, which in turn were divided into twelve indicators. The results showed that there is a significant proportion of poor households, however, their average deprivation is low, concentrating on 4 indicators linked to the economic, social and political situation in Venezuela.